Behaviour of Metakaolin Concrete in Different Curing Condition - M. N., Muhd Sidek; M. A., Megat Johari; M. F., Arshad; Mohd Faizal, Md Jaafar (Penerbit UMP, 2013)
This paper presents the result of an investigation on the effect of curing condition on concrete containing Metakaolin. Concrete grade 40 was used in this research and Metakaolin is replaced from 5%, 10% and 15%. All sample been cured by using three different curing condition which is normal curing (+20o C), expose curing (28 – 34o C) and high temperature curing (+55o ). The effect of Metakaolin on concrete will be seen by physical and mechanical properties. From physical properties the effect of Metakaolin will be seen by using soundness, setting time and workability and for mechanical properties compression and flexural test will be performed. From physical test shows Metakaolin reduce the workability of concrete and hence increase the water demand in concrete mix but the addition of Metakaolin reduce the ability of cement paste to expand. This happen because the addition of Metakaolin will fill the void around the cement paste. Results from physical test are supported by testing the mechanical part. Results show that concrete containing Metakaolin improved in all curing condition except for high temperature curing. These can be seen from compression test that shows Metakaolin increase strength of concrete except for high temperature curing. The same phenomena can be seen from flexural test. Results show the optimum replacement is at 10% and the best curing effect for Metakaolin is normal curing. Three elements that contribute to the result is the addition of Metakaolin act as a filler, accelerate the cement hydration and pozzolanic reaction that improve the physical and mechanical properties.